2010
DOI: 10.1021/la1022196
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optoelectronic Properties of Novel Films Based on Functionalized Multiwalled Carbon Nanotubes and (Phthalocyaninato)Ruthenium(II) via Coordination Bonded Layer-by-Layer Self-Assembly

Abstract: 4-(2-(4-pyridinyl)Ethynyl)benzenic diazonium salt (PBD) was used to modify multiwalled carbon nanotubes (MWCNTs) by the self-assembly technique. After the decomposition of the diazonium group in PBD under UV irradiation, the PBD monolayer film covalently anchored on multiwalled carbon nanotubes is very stable. The obtained pyridine-modified MWCNTs (Py(Ar)-MWCNTs) have good solubility in common organic solvents. Furthermore, the layer-by-layer (LBL) self-assembled fully conjugated films of Py(Ar)-MWCNTs and (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…At the beginning, only electrostatic interactions were utilized for LbL assembly. Subsequently, other interactions such as covalent bond,38–44 hydrogen bonding,45–51 charge transfer,52, 53 hydrophobic,54–56 host–gest,57–60 and coordination bond61–67 interactions have been investigated to facilitate polymer association for ultrathin film deposition. The most important concept for LbL assembly is how to use the interactions between the polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning, only electrostatic interactions were utilized for LbL assembly. Subsequently, other interactions such as covalent bond,38–44 hydrogen bonding,45–51 charge transfer,52, 53 hydrophobic,54–56 host–gest,57–60 and coordination bond61–67 interactions have been investigated to facilitate polymer association for ultrathin film deposition. The most important concept for LbL assembly is how to use the interactions between the polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sidewall of CNTs presents an excellent platform for chemical functionalisation, which allows overcoming the problem of processability (Niyogi et al 2002, Pantarotto et al 2003). For instance, MWCNTs can be functionalised with carboxyl groups to improve their dispersion in water (Zhao et al 2010). …”
mentioning
confidence: 99%
“…Just deposited twice, the quartz substrate significantly darkened, because of the strong absorption of the deposited MWNTs in the visible region, 48 which showed it was an effective way for the MWNTs LBL film formation by using the multiple hydrogen bonding as the driving force. In addition, from the inset illustrated in Figure 4, it was shown that the absorbance centered at 260 nm and the optional point at 400 nm both increase linearly with the increase of the number of deposited layers.…”
Section: Resultsmentioning
confidence: 99%